Ramsay-Hunt Syndrome with Cranial Polyneuropathy and Severe Dysphagia: A Rare and Multidisciplinary Entity - Pedrosa Rocha, Gustavo (2024)
Ramsay-Hunt syndrome is defined by varicella-zoster virus (VZV) reactivation in the geniculate ganglion of the facial nerve and its presentation involves otalgia, vesicular lesions of the outer ear and ipsilateral facial paralysis. Cranial polyneuropathy extension is rare, can sometimes take a challenging and delayed diagnosis and poor prognosis.We illustrate a case of varicella zoster virus cranial polyneuropathy affecting V, VII, VIII, IX and X cranial nerves and consequent symptomatology that led to prolonged hospitalization with multidisciplinary approach. Despite the poor prognosis, the patient had a significant clinical and imagiological improvement. Prevention and attenuation of VZV and its complications are becoming increasingly possible and the increase in knowledge about this disease for the population and physicians can have a significant impact.